Environmental and pedological factors influencing organic carbon storage in Italian forest soils - Anna Andreetta; Stefano Chelli; Eleonora Bonifacio; Roberto Canullo; Guia Cecchini; Stefano Carnicelli (Geoderma Regional, 2023)

Reconstruction scheme for excitatory and inhibitory dynamics with quenched disorder: application to zebrafish imaging - Lorenzo Chicchi; Gloria Cecchini; Ihusan Adam; Giuseppe de Vito; Roberto Livi; Francesco Saverio Pavone; Ludovico Silvestri; Lapo Turrini; Francesco Vanzi; Duccio Fanelli (Journal of Computational Neuroscience, 2021)
An inverse procedure is developed and tested to recover functional and structural information from global signals of brains activity. The method assumes a leaky-integrate and fire model with excitatory and inhibitory neurons, coupled via a directed network. Neurons are endowed with a heterogenous current value, which sets their associated dynamical regime. By making use of a heterogenous mean-field approximation, the method seeks to reconstructing from global activity patterns the distribution of in-coming degrees, for both excitatory and inhibitory neurons, as well as the distribution of the assigned currents. The proposed inverse scheme is first validated against synthetic data. Then, time-lapse acquisitions of a zebrafish larva recorded with a two-photon light sheet microscope are used as an input to the reconstruction algorithm. A power law distribution of the in-coming connectivity of the excitatory neurons is found. Local degree distributions are also computed by segmenting the whole brain in sub-regions traced from annotated atlas.

Influence of specific fermentation conditions on natural microflora of pomace in “Grappa” production - Lucilla Iacumin; Marisa Manzano; Francesca Cecchini; Sandi Orlic; Roberto Zironi; Giuseppe Comi (World Journal of Microbiology and Biotechnology, 2012)

Enterococcus spp. produces slime and survives in rat peritoneal macrophages - Lucilla Baldassarri; Roberto Cecchini; Lucia Bertuccini; Maria G. Ammendolia; F. Iosi; Carla R. Arciola; Lucio Montanaro; Roberta Di Rosa; Giovanni Gherardi; Giordano Dicuonzo; Graziella Orefici; Roberta Creti (Medical Microbiology and Immunology, 2001)